Tuberkulosis Paru Asimtomatik dengan Asites yang Disebabkan oleh Tuberkulosis Usus: Laporan Kasus - Ginting, Heri Krisnata; Simanjuntak, Arya Marganda; Humairoh, Latifah (Majalah Kedokteran Indonesia, 2025)
Introduction: Tuberculosis (TB) is usually suspected when the patient has symptoms. Ascites is generally suspected if the patient has liver disease, organ failure or malignancy. In this case, we found something that is not usually found and is an important lesson. Case Report: Mrs. RS, a 58-year-old woman, presented with abdominal swelling worsening 5 days before admission with red bloody stools. Previous USG in another hospital showed no abnormalities were found. On physical examination, a right upper lung with ronchi and weak percussion was discovered. The abdomen was distended, and there was a throbbing pain and dull ache that moved about. The bilirubin, stool analysis, and liver function values were all normal. While GeneXpert sputum was negative, abdominal ultrasound revealed ascites, stool samples were positive for TB bacteria, and chest X-ray revealed cavities in the right upper lung. Following treatment with isoniazid (R), rifampicin (R), pyrazinamide (Z), and ethambutol (E), the patient was released and instructed to await examination by the physician. Case Discussion: Although clinical signs like coughing and shortness of breath are frequently used to diagnose tuberculosis, this case was discovered to be silent pulmonary TB, which Kendall et al characterized as subclinical TB infection. Conclusion: Ascites as a result of intestinal TB is rare but possible. Increased TB suspicion testing is necessary, particularly in locations where the disease is prevalent. Instances of intestinal tuberculosis and pulmonary TB without respiratory symptoms make treating tuberculosis cases more difficult.